Digital Inclusion VS Digital Sovereignty: RRI as a Platform for Integrating Ethics into Geopolitics - Gurov, Oleg (YSU Journal of International Affairs, 2025)
The rapid advancement of artificial intelligence (AI) has intensified the global tension between digital inclusion, which advocates for equitable access to technology, and digital sovereignty, emphasizing national control over data and infrastructure. This article examines how Responsible Research and Innovation (RRI) can reconcile these competing imperatives by embedding ethical principles, such as inclusivity, sustainability, precaution, and reflexivity, into technology governance. Through qualitative case studies in education (e.g., Kenya’s eLimu and India’s DIKSHA platforms) and healthcare (e.g., WHO’s pandemic data-sharing protocols), the study demonstrates that RRI fosters participatory design, balances sovereignty with global collaboration, and mitigates systemic biases. Findings reveal that rigid sovereignty policies often exacerbate inequalities, while RRI-driven frameworks enable marginalized communities to co-create solutions, ensuring culturally relevant and ethically aligned technologies. The analysis highlights RRI’s potential to transform geopolitical competition into equitable governance, advocating for its institutionalization through international mechanisms such as the UN’s Global Digital Compact. By prioritizing social justice, RRI redefines sovereignty as a stewardship obligation, ensuring AI development uplifts, rather than undermines, vulnerable populations. The article concludes that integrating RRI principles into both global and local agendas is crucial for dismantling digital hierarchies and promoting inclusive innovation.